Morphological Variations of an Atypical Cleft Hand: A Cadaveric Case Report - Sirasanagandla, Srinivasa Rao; Al Mushaiqri, Mohamed; Al Khabori, Hussein Saleem Jawad; Al Rashdi, Roaa Abdullah Mohsin (Journal of Morphological Sciences, 2019)
Cleft hand is a group of hand deformities in which the central digits of the hand are congenitally absent. The soft tissue variations of cleft hand are rarely described. Hence, we report the anatomic variants of a unilateral atypical cleft hand with the absence of all of the phalanges of the middle finger. The 2nd and 3rd lumbricals showed a variation in their distal attachment. Both the superficial and deep flexor digital tendons of the missing middle finger were fused and inserted into the palmar surface of the head of the 3rd metacarpal bone. The extensor digitorum tendon of the missing finger was inserted on the dorsal surface of the head of the 3rd metacarpal bone. The palmar digital nerves of the median nerve of the middle finger formed 2 visible fibrotic masses; radial and ulnar, over the base of the 2nd web space. Of these, the radial mass was formed by the fusion of both palmar digital nerves and the common palmar digital artery. The knowledge of soft tissue abnormalities reported here is clinically important to plastic surgeons while restoring the good grasp and pinch of the cleft hand. The occurrence of fibrotic masses reported in the present case is unique, and these masses may cause diagnostic errors during an angiographic procedure.
Keywords: lumbrical; cleft hand; variation; plastic surgeon; deformity